Antonin Artaud and Gilles Deleuze’s Philosophy of Modern Cinema - Baranova, Jūratė (Problemos, 2014)
The article aims to decipher the traces of Antonin Artaud’s (1898-1948) ideas in Gilles Deleuze’s (1925–1995) philosophy of modern cinema, expressed in Cinema 2, L‘Image-Temps. The paper focuses on the following questions: In what sense Deleuze’s experimentation with Artaud’s ideas in the chapter VII. La pensée et la cinéma differs from his approach towards the ideas of the Russian film director Sergei Eisenstein? How do Artaud’s reflections about the l‘impouvoir de la pensée work in Deleuz’s text? Has Artaud’s reflection on body without organs anything to do with two possible bodies (body of poses and body of ceremonies) that Deleuze has discerned as the signs of modern cinema? The author of the article comes to the conclusion that it is possible to discern two conceptions of a body that Deleuze borrowed from Artaud: pre-schizophrenic body of poses and gestures, which constitutes the conceptual core of the theatre of cruelty, the other one – schizophrenic body without organs. The latter influenced Deleuze’ss research together with Guattari, the former – his conceptual presuppositions for philosophizing on modern cinema. The main thesis of this article is that it is not possible to neglect and not notice Artaud’s influence on Deleuze’s film philosophy when discussing the theorethical sources of his philosophy of modern cinema.